Prevalence and epidemiological characteristics of asymptomatic malaria in Sucre, Venezuela: a 2022 cross-sectional study - Jessica L. Leyva; Paola A. Pereira-Leitao; Gabriel E. García-Meléndez; Samuel De Amicis; Rodrigo Celis; Mariana Hidalgo; Antonio Hernández; Fhabián S. Carrión-Nessi; David A. Forero-Peña (Malaria Journal)
Abstract Background Despite a significant reduction in malaria cases in America, Venezuela has experienced a substantial increase between 2000 and 2019. Asymptomatic malaria, prevalent in both low- and high-endemic regions, poses a challenge due to the absence of clinical manifestations and often low parasitaemia. This study aims to determine the current prevalence of asymptomatic malaria in four rural communities of Sucre, the third most endemic state in the country. Methods A community-based cross-sectional study was conducted from October to December 2022 (high seasonality period). Individuals were interviewed in their households and assessed for malaria using rapid diagnostic tests (RDTs), thick and thin blood smear microscopy, and polymerase chain reaction (PCR). Asymptomatic individuals with PCR positive (PCR+) for Plasmodium were classified as cases, while PCR negative individuals were classified as controls. Descriptive statistics were used to analyse the data. The normality of numerical variables was assessed with the Kolmogorov–Smirnov test. Based on this assessment, Student’s t-test was applied to normally distributed variables and Mann–Whitney U-test to non-normally distributed ones. For categorical variables, Pearson’s chi-square test was used when less than 25.0% of cells had an expected frequency below five; otherwise, Fisher’s exact test was employed. Results The study involved 351 individuals, mostly women (54.7%), of mixed (non-indigenous) race (61.3%), with primary (6 years) education (40.7%). The most common occupations were students (30.5%), housekeepers (27.6%), and farmers (16.5%). Over half (54.4%) had lived at their current address for over 10 years. The prevalence of asymptomatic malaria by RDTs and microscopy was 0.3% (n = 1/351) as determined. However, PCR detected a higher prevalence of 24.8% (87 positive cases, 95.0% CI = 20.5–29.5), primarily caused by P. vivax (73.6%). The highest prevalences were observed in individuals aged over 15 years (27.1%, 95.0% CI = 21.6–33.1), males (28.3%, 95.0% CI = 21.7–35.6), those with a college (14 years) education (33.3%, 95.0% CI = 17.2–53.2), and educators (41.7%, 95.0% CI = 18–68.8). The rural community with the highest prevalence was Chacopata (30.6%, 95.0% CI = 17.4–46.7), followed by El Paujil (28.6%, 95.0% CI = 21.9–36.1), Yaguaraparo (23.2%, 95.0% CI = 15.1–33.1), and Cristóbal Colón (16.5%, 95.0% CI = 9.6–25.8). Two-thirds (66.7%) reported a malaria history, predominantly caused by P. vivax (70.5%), with a median of 3 previous episodes. At least one-third (35.5%) had non-adherence to treatment during their most recent malarial episode. No statistically significant differences were observed between sociodemographic characteristics and malaria history of individuals with asymptomatic malaria (PCR+) and controls. Conclusion RDTs and microscopy only managed to diagnose less than 1.0% of asymptomatic malaria cases. Active surveillance systems with high sensitivity such as PCR may provide accurate estimates of asymptomatic malaria prevalence needed for opportune diagnosis and treatment.